Influence of Cryoconcentration on Quality Attributes of Apple Juice (Malus Domestica cv. Red Fuji) - Patricio Orellana-Palma; Virgilio Lazo-Mercado; María Pía Gianelli; Eduard Hernández; Rommy N. Zúñiga; Guillermo Petzold (Applied Sciences, 2020)
Apple juice was subjected to centrifugal block cryoconcentration (CBCC) for three cycles and their effect on the physicochemical properties, bioactive compounds, antioxidant activity, volatile profile, and sensory analysis was investigated. In the final cycle, the solutes were approximately four-fold of the initial condition (≈14 °Brix) and the color (ΔE* ≈ 25.0) was darker than the fresh juice, with bioactive compound concentration values close to 819 mg GAE/100 g d.m., 248 and 345 mg CEQ/100 g d.m. for total polyphenol, flavonoid, and flavanol content, respectively, equivalent to a retention of over 60%. DPPH and FRAP assays presented high antioxidant activities, with values of approximately 1803 μmol TE/100 g d.m. and 2936 μmol TE/100 g d.m, respectively. The cryoconcentrate showed a similar aromatic profile to the fresh juice, with 29 and 28 volatile compounds identified, respectively. The centrifugal force allowed to obtain excellent process parameters, with 73%, 0.87 (kg/kg), and 85% for efficiency, solute yield, and percentage of concentrate, respectively. Sensory evaluation shows that the odor, aroma, and flavor of fresh sample were remained in the reconstituted cryoconcentrate sample, with good qualifications (four points in a five-score hedonic scale) by trained panelists. Therefore, CBCC can preserve important quality attributes from apple juice.